Understanding and treating adolescent substance abuse - Muisener, Philip P.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1994)
Biological, psychological and social factors are considered in the author's exploration of adolescent substance abuse, with adolescents presented as a clearly defined group with unique needs and concerns. Assessment, treatment planning, service provision and the recovery process are all considered.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Teenagers -- Drug use -- United States; Teenagers -- Drug use -- United States -- Prevention; Teenagers -- Alcohol use -- United States; Teenagers -- Alcohol use -- United States -- Prevention; Drug abuse -- Treatment -- United States; Alcoholism -- Treatment -- United States; Electronic books